FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KOTA SEMARANG - Krisbianti, Dian; Maryono, Maryono (Jurnal Riset Akuntansi Politala, 2024)
The number of motorized vehicles in the city of Semarang increased by 129,800 units from 1,382,434 units in 2020 to 1,512,234 units in 2021. Local tax revenue could increase with the compliance of taxpayers in paying taxes. The research aims to examine the variables influencing taxpayers' compliance with motor vehicle tax payments, specifically in the city of Semarang. Primary data was collected through a questionnaire distributed via Google Forms. The data collection technique was adjusted to the source of the data, and the questionnaire was distributed to respondents online through a provided link. The sampling technique was based on convenience, targeting individuals who met the researcher and fulfilled the predefined criteria, such as owning a motorized vehicle, being registered at the Semarang city tax office (samsat), and having used the E-Samsat service to pay motor vehicle taxes. The researcher used SPSS 22 as a tool for multiple linear regression analysis in the study. Based on the processed data, the researcher found that the tax knowledge variable has a positive influence on taxpayers' compliance. However, the variables of education level and the implementation of E-Samsat showed no significant impact on taxpayers' compliance.